Analisis Penentuan Daerah Rawan Kecelakaan (Blacksite) di Kabupaten Sidoarjo - Renaldo P, cristofer; Theresia, Theresia (Jurnal Etnik: Ekonomi-Teknik, 2023)
The development of highways gave birth to something inseparable from human growth and technological progress: In addition, roads also play a role in the growth of society’s economy. Traffic accidents are unforeseen or unintentional events on the road involving vehicles or other road users and resulting in human casualties or loss of property. There are several points in the district of Sidoarjo according to the accident data of January 2022 s/d January 2023 obtained from the Lantas Polresta Sidoarjo unit.Based on the data, it can be calculated using the accident equivalent number method to know the size of the accident number in the area, as well as the method of Upper Limit Control and Upper Control limit, in order to obtain the area vulnerable to accidents in the district of Sidoarjo.The results of the analysis showed that identified 4 areas vulnerable to accidents, namely Park, Balongbendo, Sidoarjo, and Prambon. The value of the park accident equivalent number of 252 points of the UC and BKA values (BKA = 131 and UCL = 130), the AEK Value 150 is higher than the control limit (BCA = 131 and UCL = 123), the AEK Sidoarjo 168 is greater than the control limit (BKa = 131 and UCL = 124), and AEK Prambon 135 is higher than the control limits (Bka = 131 and UCL = 122).